2018
DOI: 10.1002/aenm.201801537
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Factors Determining the Efficiency of Photocurrent Generation in Polymer:Nonfullerene Acceptor Solar Cells

Abstract: 3 years, NFA-based OSC performance has improved remarkably, with several studies reporting efficiencies over 13% driven primarily through improved molecular design. [4][5][6][7] Particular progress has been made in enhancing the open circuit voltage (V OC ) of OSCs, achieved by use of NFAs with higher the lowest unoccupied molecular orbital (LUMO) levels as well as suppression of nonradiative recombination losses. [8][9][10][11][12][13][14] However, progress in achieving improvements in photocurrent generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 54 publications
3
36
0
Order By: Relevance
“…For homogeneous media, theory predicts a CT binding energy of around 400 meV, in clear contrast to the high external quantum efficiency (EQE) for photocurrent generation of many NFA‐containing devices. Several studies showed high EQE to be related to a larger driving force . This situation reminds of the “hot” dissociation model, where exciton dissociation creates a more loosely bound electronically/vibronically excited CT state .…”
mentioning
confidence: 72%
“…For homogeneous media, theory predicts a CT binding energy of around 400 meV, in clear contrast to the high external quantum efficiency (EQE) for photocurrent generation of many NFA‐containing devices. Several studies showed high EQE to be related to a larger driving force . This situation reminds of the “hot” dissociation model, where exciton dissociation creates a more loosely bound electronically/vibronically excited CT state .…”
mentioning
confidence: 72%
“…Cha et al attributed this to the smaller driving force for charge separation and a greater degree of geminate recombination in PffBT4T-2OD:EH-IDTBR. 9,27 However, in-depth analysis of the transient absorption (TA) data has not been performed. The exciton and charge dynamics as well as the dynamics of CTS have not been clearly identified.…”
Section: Article Scitationorg/journal/jcpmentioning
confidence: 99%
“…[48] A strong NFA π-π stacking has been reported to enhance charge transport, but not linked systematically with charge generation. [48] Therefore ultrafast spectroscopic studies have shown that charge carriers are also generated efficiently in NFA-based OSCs, [35][36][37][38][39][40] but a detailed photophysical understanding of NFA OSCs still lags behind the continuing, very promising, advances in their device efficiencies.…”
Section: Introductionmentioning
confidence: 99%